2015
DOI: 10.1021/acs.inorgchem.5b01857
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Chlorate–Bromide Reaction

Abstract: The chlorate-bromide reaction, ClO3(-) + 6Br(-) + 6H(+) → 3Br2 + Cl(-) + 3H2O, was followed at the Br3(-)/Br2 isosbestic point (446 nm). A fifth-order rate law was found: (1)/3 d[Br2]/dt = k[ClO3(-)][Br(-)][H(+)](3) (k = 5.10 × 10(-6) s(-1) L(4) mol(-4)) at 25 °C and I = 2.4 mol L(-1). At high bromide concentrations, the bromide order becomes close to zero, indicating a saturation profile on bromide concentration, similar to the chloride saturation profile observed in the chlorate-chloride reaction. A mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Step is the other rate-determining step of the proposed model, producing OClOIO 3 , a key intermediate of the reaction. Similar oxyhalogen intermediates have already been well-established in the case of the Dushman reaction, as well as those of the chlorite–hypochlorous acid, chlorate–chloride, periodate–bromide, and chlorate–bromide reactions. By an analogy, we therefore propose here OClOIO 3 .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Step is the other rate-determining step of the proposed model, producing OClOIO 3 , a key intermediate of the reaction. Similar oxyhalogen intermediates have already been well-established in the case of the Dushman reaction, as well as those of the chlorite–hypochlorous acid, chlorate–chloride, periodate–bromide, and chlorate–bromide reactions. By an analogy, we therefore propose here OClOIO 3 .…”
Section: Discussionsupporting
confidence: 65%
“…As a result the last couple of decades have witnessed intense studies of various oxyhalogen-based systems via monitoring the reactants, intermediates, and/or products by different spectroscopic techniques such as UV–vis and stopped-flow technique in order to establish reliable kinetic models and to obtain thorough insight into their mechanisms. The list, of course, does not end here; further examples of such systems as the bromate–chlorite, hypochlorous acid–chlorite, chlorate–bromide, chlorate–chloride, iodide–iodate, and periodate–bromide reactions may also be provided after a survey of the literature. Checking the reported mechanisms of these systems has revealed that crucial short-lived intermediates (halogen oxides with different compositions) are considered to be involved for explanation of the kinetic behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model results were compared to the absorbance versus time curves obtained experimentally using different concentration of the reactants. The entire procedure is analogous to that used in the similar kinetic study of chlorate–bromide reaction made recently by our group …”
Section: Methodsmentioning
confidence: 98%
“…The entire procedure is analogous to that used in the similar kinetic study of chlorate−bromide reaction made recently by our group. 16 ■ RESULTS AND DISCUSSION…”
Section: ■ Experimental Sectionmentioning
confidence: 99%